From Car-Dependent Neighborhoods to Walkers' Paradise: Estimating Walkability Premiums in the Condominium Housing Market. Issue 1 (January 2014) - Li, Wei; Joh, Kenneth; Lee, Chanam; Kim, Jun-Hyun; Park, Han; Woo, Ayoung
Movement toward compact and walkable communities and low-carbon travel has gained momentum through various policy initiatives. However, residents' willingness to pay for neighborhood walkability is still unknown. This study addresses that knowledge gap by quantifying walkability premiums based on 3, 899 condominium sale transactions from 2010 to 2012 in Austin, Texas. Two measures of walkability were compared: Walk Score and Street Smart Walk Score. A spatial hedonic modeling approach improved estimation accuracy by controlling for spatial autocorrelation effects. The premium for walkability was found to be influenced by the pedestrian collision rate, street connectivity, length of sidewalks, speed limit, and various sociodemographic factors. A positive walkability premium was identified for 57% of sampled condominiums, most of which were located in neighborhoods that were at least somewhat walkable. The results could be used to identify investment priorities for creating walkable neighborhoods.